Truck drivers' perceptions on wearable devices and health promotion: a qualitative study - Rama Greenfield; Ellen Busink; Cybele P. Wong; Eva Riboli-Sasco; Geva Greenfield; Azeem Majeed; Josip Car; Petra A. Wark (BMC, 2016)
Abstract Background Professional truck drivers, as other shift workers, have been identified as a high-risk group for various health conditions including cardiovascular disease, obesity, diabetes, sleep apnoea and stress. Mobile health technologies can potentially improve the health and wellbeing of people with a sedentary lifestyle such as truck drivers. Yet, only a few studies on health promotion interventions related to mobile health technologies for truck drivers have been conducted. We aimed to explore professional truck drivers' views on health promotion delivered via mobile health technologies such as wearable devices. Methods We conducted a phenomenological qualitative study, consisting of four semi-structured focus groups with 34 full-time professional truck drivers in the UK. The focus groups were audio-taped, transcribed verbatim and analysed using thematic content analysis. We discussed drivers' perceptions of their health, lifestyle and work environment, and their past experience and expectations from mobile health technologies. Results The participants viewed their lifestyle as unhealthy and were aware of possible consequences. They expressed the need and wish to change their lifestyle, yet perceived it as an inherent, unavoidable outcome of their occupation. Current health improvement initiatives were not always aligned with their working conditions. The participants were generally willing to use mobile health technologies such as wearable devices, as a preventive measure to avoid prospect morbidity, particularly cardiovascular diseases. They were ambivalent about privacy and the risk of their employer's monitoring their clinical data. Conclusions Wearable devices may offer new possibilities for improving the health and wellbeing of truck drivers. Drivers were aware of their unhealthy lifestyle. They were interested in changing their lifestyle and health. Drivers raised concerns regarding being continuously monitored by their employer. Health improvement initiatives should be aligned with the unique working conditions of truck drivers. Future research is needed to examine the impact of wearable devices on improving the health and wellbeing of professional drivers.